2020
DOI: 10.1088/1361-6595/ab94d3
|View full text |Cite
|
Sign up to set email alerts
|

Fully ionized nanosecond discharges in air: the thermal spark

Abstract: The formation and decay of the thermal spark generated by a single nanosecond highvoltage pulse between pin electrodes are characterized in this study. The influence of air pressure in the range 50 -1000 mbar is investigated at 300 K. By performing short-gate imaging and Optical Emission Spectroscopy (OES), we find that the thermal sparks exhibit an intense emission from excited electronic states of N + , in contrast with non-thermal sparks for which the emission is dominated by electronic transitions of N2. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
107
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(136 citation statements)
references
References 65 publications
26
107
3
Order By: Relevance
“…The electron number density, measured by Stark broadening of N + , reached ne = 9×10 18 cm -3 , representing an ionization of 36%. Such high electron number densities and temperatures were also measured by other teams in pin-to-pin configurations [10][11][12][13][14] and nanosecond Dielectric Barrier Discharges [15,16].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The electron number density, measured by Stark broadening of N + , reached ne = 9×10 18 cm -3 , representing an ionization of 36%. Such high electron number densities and temperatures were also measured by other teams in pin-to-pin configurations [10][11][12][13][14] and nanosecond Dielectric Barrier Discharges [15,16].…”
Section: Introductionsupporting
confidence: 62%
“…In a previous work [13], we compared our results to the literature and demonstrated that, in pin-to-pin configurations, thermal sparks are generated in five stages:…”
Section: Introductionmentioning
confidence: 93%
“…The temperature in the plasma T gas,plasma ≈ 3500 K, higher than the adiabatic flame temperature (T ad < 2100 K), and the dissociation of O 2 indicate that this discharge is neither an NRP-corona nor an NRP-glow discharge [13]. n e is between the values reported for nonequilibrium NRP-sparks [12], and for thermal sparks [21]. As neither N + emission (500 nm) nor an electron continuum is observed in the spectra, the NRPspark is necessarily of the nonequilibrium type.…”
Section: Characterization Of the Plasmamentioning
confidence: 69%
“…A 6-meter long coaxial cable (75 Ω impedance) connects the generator and the electrode. A high voltage probe (Lecroy PPE20kV) and a current probe (Pearson 6585) are placed midway on the cable and are used to monitor the deposited energy on an oscilloscope (Lecroy HDO 6104) [21]. Typical voltage and current curves are shown in Fig.…”
Section: Measurement Equipmentmentioning
confidence: 99%
See 1 more Smart Citation